2010
DOI: 10.1016/j.aap.2009.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Explaining variation in safety performance of roundabouts

Abstract: The conversion of an intersection into a roundabout has been proven to reduce generally the number of crashes with injuries or fatalities. However, evaluation studies frequently showed considerable individual differences in safety performance of roundabouts or particular groups of roundabouts. The main purpose in the present study was to explain the variance in safety performance of roundabouts through the use of state-of-the-art cross-sectional risk models based on crash data, traffic data and geometric data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
64
3
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(76 citation statements)
references
References 17 publications
8
64
3
1
Order By: Relevance
“…Generally, it was found that roundabouts are able to reduce injury crashes considerably, although not for all user groups (Daniels et al, 2008;2009;Elvik, 2003;Persaud et al, 2001). In a previous analysis by the same authors, crash prediction models were fit for all injury crashes at roundabouts (Daniels et al, 2010.). The results showed that vulnerable road users (moped riders, motorcyclists, bicyclists and pedestrians) are more frequently than expected involved in crashes at roundabouts.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Generally, it was found that roundabouts are able to reduce injury crashes considerably, although not for all user groups (Daniels et al, 2008;2009;Elvik, 2003;Persaud et al, 2001). In a previous analysis by the same authors, crash prediction models were fit for all injury crashes at roundabouts (Daniels et al, 2010.). The results showed that vulnerable road users (moped riders, motorcyclists, bicyclists and pedestrians) are more frequently than expected involved in crashes at roundabouts.…”
Section: Introductionmentioning
confidence: 89%
“…The dataset departed from a previously composed dataset of 90 roundabouts (Daniels et al, 2010), that was extended. Each roundabout in the sample was visited and photographed, traffic counts were executed and geometric data were collected on the spot.…”
Section: Data Collectionmentioning
confidence: 99%
“…The most radical measures refers to segregate lanes, which has been proved to be an efficient solution to protect riders from conflicts with cars and trucks, the greatest benefit of this solution being got when the PTW traffic overcome a certain level (according to Radin Umar, Mackay and Hills [25]: 15,000 vehicles a day with a proportion between 20% and 30% of PTWs in the traffic). But less massive solutions can also be promoted to avoid critical interactions with cars in town, such as replacing intersections, known to be detrimental to PTWs, with roundabouts, but considering the necessity to adapt them to avoid PTWs single vehicle crashes when negotiating them [26].…”
Section: Discussionmentioning
confidence: 99%
“…Although rare, this phenomenon can arise when the sample size is very small, leading to erroneous parameter estimates [24] [25]. To address the limitations of NB models, Poisson-lognormal models have been proposed, in which the error term is Poisson-lognormal rather than gamma-distributed to better handle the under-dispersed crash counts [21] [26] [27]. Another widely used type of crash prediction model is the zero-inflated Poisson and zero-inflated negative binomial models, which have been introduced mainly to deal with the over-dispersion problem caused by excessive zeroes (i.e.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To address the limitations of the NB models, the Poisson-lognormal model was introduced, in which the error term is Poisson-lognormal rather than gammadistributed so as to better handle under-dispersed data counts [21] [26] [27]. The Poisson-lognormal model is similar to the negative binomial model, however, the EXP (ε i ) term used in the model is lognormal-rather than gamma-distributed.…”
Section: Poisson-lognormal Regression Modelmentioning
confidence: 99%